2021
DOI: 10.1111/1754-9485.13357
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and radiotherapy patterns of care in the management of breast cancer in NSW and ACT Australia

Abstract: Introduction This study aims to report on the surgical and radiotherapy patterns of breast cancer care in New South Wales (NSW) and Australian Capital Territory (ACT) in Australia, to identify factors that impact on utilisation of evidence‐based treatment and to report on the overall survival (OS) rate and the influencing factors on OS. Methods Cancer registry data linked to hospital records for all patients with breast cancer diagnosis in NSW and ACT between 2009 and 2014 were used to calculate rates of breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…20,24 For breast cancer, our data resemble published data from both Australia and the US where most patients with non-metastatic breast cancer undergo surgery. 20,25,26 Rates of surgical treatment were greatest in this group, likely due to the use of relatively low-risk breastconserving procedures. Our cohort received slightly less radiation therapy than that reported in a younger Australian cohort (median age 61 versus 74.6 years) where 63% received radiation therapy.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…20,24 For breast cancer, our data resemble published data from both Australia and the US where most patients with non-metastatic breast cancer undergo surgery. 20,25,26 Rates of surgical treatment were greatest in this group, likely due to the use of relatively low-risk breastconserving procedures. Our cohort received slightly less radiation therapy than that reported in a younger Australian cohort (median age 61 versus 74.6 years) where 63% received radiation therapy.…”
Section: Discussionmentioning
confidence: 91%
“…Our cohort received slightly less radiation therapy than that reported in a younger Australian cohort (median age 61 versus 74.6 years) where 63% received radiation therapy. 25 Rates of radiation therapy were still the highest for the six commonest cancers, an expected finding given the widespread use of adjuvant radiation in localised or regional breast cancers. 20 In those with metastatic disease, rates of chemotherapy (31%) and hormonal therapy (63%) resemble the rates of large European and North American cohorts.…”
Section: Discussionmentioning
confidence: 97%
“…In Australia, just under 70% of women undergo breast conservation 30 . Mastectomy is largely reserved for those with large volume or multifocal disease, if radiation is contraindicated, or for patient preference 30 . If mastectomy is undertaken, breast reconstruction can often be offered, which is either done by the breast surgeon or in combination with a plastic reconstructive surgeon.…”
Section: Treating Breast Cancer: Evolution Of Surgical Managementmentioning
confidence: 99%
“…Randomised trials confirmed that, for many women with breast cancer, breast‐conserving treatment (“lumpectomy”, usually with whole breast radiation) is at least as good if not superior to mastectomy in terms of survival, with excellent local control 29 . In Australia, just under 70% of women undergo breast conservation 30 . Mastectomy is largely reserved for those with large volume or multifocal disease, if radiation is contraindicated, or for patient preference 30 .…”
Section: Treating Breast Cancer: Evolution Of Surgical Managementmentioning
confidence: 99%
See 1 more Smart Citation